Making Charcoal Briquettes from Corncobs Organic Waste Using Variation of Type and Percentage of Adhesives - Lilih Sulistyaningkarti; Budi Utami (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
This study aimed to (1) make charcoal briquettes from corncobs organic waste; (2) determine the right type of adhesive to make a corncobs charcoal briquette to produce good quality briquettes; (3) determine the appropriate percentage of adhesive to produce corncobs briquettes to produce good quality briquettes; and (4) know the best characteristics of corncobs charcoal briquettes which include moisture content, volatile content, ash content, carbon content and caloric value. The sample used was corncob obtained from a corn farmer in Pasekan Village, Wonogiri regency. This research used experimental method in laboratory with several stages, namely: (1) preparation of materials; (2) carbonization; (3) crushing and sifting of charcoal (4) mixing charcoal with adhesive and water; (5) briquetting; (6) briquette drying; And (7) analysis of briquette quality. This adhesive types used in this research were tapioca flour and wheat flour and the percentage of adhesive material were 5%, 10% and 15% from total weight of charcoal powder. The result of the research were: (1) charcoal briquettes as alternative energy source can be made from biomass waste (corncobs organic waste); (2) charcoal briquettes from organic corncobs wastes using tapioca flour adhesives have better quality than using wheat flour adhesives; (3) the both charcoal briquettes using 5% of tapioca flour adhesive and 5% wheat flour adhesives have better quality than 10% and 15% in terms of moisture content, volatile content, ash content, carbon content and calorific value; and (4) the best characteristics obtained are for the charcoal briquettes using 5% of tapioca flour adhesive, which have water content of 3,665%; volatile matter amounting of 11.005%; ash content of 4.825%; fixed carbon content of 80.515%; and high heat value of 5661,071%.